Las principales tecnologías de la era de la industria 5.0 - Pérez Domínguez, Luis (2024)
Currently, the industrial environment and society in general is in the dynamics of Industry 4.0, which is laying the foundations for the next industrial revolution. At the same time, the global health difficulties derived from COVID-19 are causing companies to look for solutions to continue operating, this situation in any case, causing industry 5.0 to take an exponential leap, causing companies to implement new manufacturing processes. Therefore, this new industrial revolution consists of taking advantage of and developing artificial intelligence to give way to the main characteristic that defines it, which is the collaboration between man and machine, working together while machines perform the heaviest and most repetitive tasks. Likewise, people are in charge of monitoring activities. Additionally, one of the fundamental elements of I.5 are industrial cobots (robotic system instituted to work together with humans) although cobots and other elements regardless of the main topic, there are also other very important aspects such as society 5.0 and the bioeconomy. In this way, this is why the main objective of this research is to present the transcendental technologies in Industry 5.0.